2011
DOI: 10.1021/la200429j
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Film-Formation Dilemma with Infrared Radiation-Assisted Sintering

Abstract: The film formation of an acrylate latex with a glass transition temperature of 38 °C has been achieved through the use of near-infrared (NIR) radiative heating. A hard, crack-free coating was obtained without the addition of plasticizers. Sintering of acrylate particles was confirmed through measurements using atomic force microscopy. The addition of an NIR-absorbing polymer increased the rate of particle deformation such that it was significantly greater than obtained in a convection oven at 60 °C. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…[20,21] Upon continued exposure to IR radiation, the dry particles coalesce, driven by the reduction of the surface energy of the polymer/air interface. [12] When the interparticle voids are closed, the coating becomes optically transparent. The evaporation rates have been measured as a function of the power of the emitter (Fig.…”
Section: Characterization Of Water Loss Under Ir Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,21] Upon continued exposure to IR radiation, the dry particles coalesce, driven by the reduction of the surface energy of the polymer/air interface. [12] When the interparticle voids are closed, the coating becomes optically transparent. The evaporation rates have been measured as a function of the power of the emitter (Fig.…”
Section: Characterization Of Water Loss Under Ir Radiationmentioning
confidence: 99%
“…First, the heat from the radiation increases the evaporation rate locally, so that the technique is practical on realistic time-scales. Secondly, polymer particles are sintered by heating from the IR radiation [12], so that patterned coatings can be made from "hard" polymers, with a glass transition temperature far above room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…transfer (DET), [32][33][34][35][36] small-angle X-ray scattering (SAXS), 21,[37][38][39][40] atomic force microscopy (AFM) 19,41,42 and solid state NMR 42,43 haven been established to investigate latex film formation and dry particle sintering. Most of these methods need a quite elaborate experimental setup or a specific labelling with dyes/ deuterated compounds of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…The switching mechanism requires the fusing together of the hard NPs, via a sintering process, such that the percolating network of NPs is able to support stress. In latex blends of hard and soft particles, Chevalier et al reported that the elastic modulus increased by several orders of magnitude only when the hard particles were above the percolation threshold and also when the temperature was raised above the glass transition temperature of the hard particles, so that they sintered .…”
Section: Introductionmentioning
confidence: 99%